Chemipil, Inc. a plant design on the production of tannin, lignin, and furfural from ipil-ipil wood - Bustamante, Alice A.; Dimacali, Edwin D.; Herrera, Grace S. (Diliman, Quezon City College of Engineering, 1981)
Capacity: 4540 metric tons/year -- Land area: 4 hectares -- Total fixed capital investment: P 33,169,600 -- Operating cost at maximum production: P 74,806,400 -- Annual sales at maximum production: P 105,999,000 -- Pay-off period: 2.02 years -- Break even point: 2994 metric tons/year -- Shut down point: 1983 metric tons/year -- % return on investment: 33.66%
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Wood -- Chemistry; Furfural; Lignin